2021
DOI: 10.26434/chemrxiv.13559852.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cobalt Catalysis Enables Regioselective Ring-opening of Epoxides with Aryl Halides

Abstract: Ring-opening of epoxides furnishing either linear or branched products belongs to the group of classic transformations in organic synthesis. However, the regioselective cross-electrophile coupling of aryl epoxides with aryl halides still represents a key challenge. Herein, we report vitamin B12/Ni dual-catalytic system that allows for the selective synthesis of linear products under blue-light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Gryko has shown that a photo-induced Ni and VB 12 dual catalytic method was suitable for regioselective epoxide ring opening/arylation at the sterically less hindered site, analogous to that of the iodide substitution process (Scheme 3c ). 12 The nucleophilic ring opening of an epoxide by a Co(I) catalyst based on VB 12 generates an alkyl–Co(III) intermediate, which undergoes homolysis to give an alkyl radical and a Co(II) species under blue light irradiation. Reduction of Co(II) regenerates Co(I).…”
Section: Direct Single-electron Transfer To a C(sp 3 ...mentioning
confidence: 99%
“…Gryko has shown that a photo-induced Ni and VB 12 dual catalytic method was suitable for regioselective epoxide ring opening/arylation at the sterically less hindered site, analogous to that of the iodide substitution process (Scheme 3c ). 12 The nucleophilic ring opening of an epoxide by a Co(I) catalyst based on VB 12 generates an alkyl–Co(III) intermediate, which undergoes homolysis to give an alkyl radical and a Co(II) species under blue light irradiation. Reduction of Co(II) regenerates Co(I).…”
Section: Direct Single-electron Transfer To a C(sp 3 ...mentioning
confidence: 99%